Clinical adverse events to dexmedetomidine: a real-world drug safety study based on the FAERS database - Liu, Feng; Zheng, Jing-xuan; Wu, Xiao-dan (Frontiers in Pharmacology, 2024)
Objective Adverse events associated with dexmedetomidine were analyzed using data from the FDA’s FAERS database, spanning from 2004 to the third quarter of 2023. This analysis serves as a foundation for monitoring dexmedetomidine’s safety in clinical applications. Methods Data on adverse events associated with dexmedetomidine were standardized and analyzed to identify clinical adverse events closely linked to its use. This analysis employed various signal quantification analysis algorithms, including Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-Item Gamma Poisson Shrinker (MGPS). Results In the FAERS database, dexmedetomidine was identified as the primary suspect in 1,910 adverse events. Our analysis encompassed 26 organ system levels, from which we selected 346 relevant Preferred Terms (PTs) for further examination. Notably, adverse drug reactions such as diabetes insipidus, abnormal transcranial electrical motor evoked potential monitoring, acute motor axonal neuropathy, and trigeminal cardiac reflex were identified. These reactions are not explicitly mentioned in the drug’s specification, indicating the emergence of new signals for adverse drug reactions. Conclusion Data mining in the FAERS database has elucidated the characteristics of dexmedetomidine-related adverse drug reactions. This analysis enhances our understanding of dexmedetomidine’s drug safety, aids in the clinical management of pharmacovigilance studies, and offers valuable insights for refining drug-use protocols.